Legon Guru Seaside sebagai Strategi Revitalisasi Pengembangan Pariwisata Pantai Berkelanjutan di Ujung Kulon - Mukti, Titania (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
The revitalization of Legon Guru Seaside Beach aims to improve physical conditions and develop tourism potential in areas affected by the 2018 tsunami disaster due to the eruption of Mount Krakatau. The project integrates infrastructure improvement, the construction of tourist facilities, and the empowerment of local communities to achieve sustainable tourism development. This research uses a project-based practice approach that involves planning, implementation, and evaluation, by actively involving local communities at each stage. The results of this project show an improvement in the quality of beach facilities and tourist attractions. The construction of new facilities such as photo spots was built and the beach area was rearranged taking into account the principles of sustainability. In addition, this project is also equipped with training and the formation of micro business groups based on local wisdom to manage tourism open trips and produce souvenir products. Recommendations for future projects include finding additional sources of funding and expanding training programs. A holistic, participatory, and sustainable approach is key to the successful revitalization of post-disaster tourist destinations, providing a model that can be applied to similar projects in the future.